2012
DOI: 10.1016/j.antiviral.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent primuline derivatives inhibit hepatitis C virus NS3-catalyzed RNA unwinding, peptide hydrolysis and viral replicase formation

Abstract: The hepatitis C virus (HCV) multifunctional nonstructural protein 3 (NS3) is a protease that cleaves viral and host proteins and a helicase that separates DNA and RNA structures in reactions fueled by ATP hydrolysis. Li et al. (J. Med. Chem. 2012, 55:3319-3330) recently synthesized a series of new NS3 helicase inhibitors from the benzothiazole dimer component of the fluorescent yellow dye primuline. This study further characterizes a subset of these primuline derivatives with respect to their specificity, mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…To this end, we examined the effect of each compound on NS3h intrinsic protein fluorescence. Ndjomou et al recently showed that primuline derivatives quench intrinsic protein fluorescence with apparent dissociation constants in the low micromolar range similar to the IC 50 values seen in helicase assays (13). Similar results were obtained here for compounds 1, 2, 3, and titan yellow, with helicases isolated from either genotype 1b or 2a (Fig.…”
Section: Compound 1 Only Stimulates Atp Hydrolysis Catalyzed By Ns3hsupporting
confidence: 77%
See 1 more Smart Citation
“…To this end, we examined the effect of each compound on NS3h intrinsic protein fluorescence. Ndjomou et al recently showed that primuline derivatives quench intrinsic protein fluorescence with apparent dissociation constants in the low micromolar range similar to the IC 50 values seen in helicase assays (13). Similar results were obtained here for compounds 1, 2, 3, and titan yellow, with helicases isolated from either genotype 1b or 2a (Fig.…”
Section: Compound 1 Only Stimulates Atp Hydrolysis Catalyzed By Ns3hsupporting
confidence: 77%
“…These results suggest that primuline derivatives do not act nonspecifically (e.g. through protein aggregation), and that they do not inhibit helicase action simply by binding in place of ATP (13).…”
mentioning
confidence: 81%
“…Previous biochemical studies have shown that the protease domain of NS3 is required for efficient unwinding of double-stranded RNA (dsRNA) by the helicase (28), and recently, Aydin et al (19) proposed a model in which the protease domain of NS3 binds to dsRNA as a clamp while the helicase unwinds the double-stranded template to allow access by NS5B to the negative strand for RNA synthesis. It is tempting to speculate that binding of telaprevir to the protease domain may inhibit RNA synthesis by reducing helicase activity, but a previous study has reported that telaprevir does not inhibit the helicase activity of full-length NS3 in vitro (29). In vivo, however, NS3 functions as part of a multiprotein replicase complex where binding of telaprevir may result in disruption of proteinprotein and protein-RNA interactions to block a function of NS3 in RNA synthesis.…”
Section: Discussionmentioning
confidence: 95%
“…In an earlier report, Ndjomou et al (2012) 10 studied the effects of a series of benzothiazole compounds derived from the yellow dye primuline on the various functions of the HCV NS3 protein. Many of these compounds, like NIH molecular probe ML283, 16 specifically inhibit NS3-catalyzed RNA and DNA unwinding, but they do not potently inhibit the ability of NS3 to cleave ATP and peptides.…”
Section: Resultsmentioning
confidence: 99%
“…1) inhibit both the NS3 helicase and protease functions in vitro , but not the ability of NS3 to cleave ATP, the fuel for helicase movement. 10 …”
Section: Introductionmentioning
confidence: 99%